2021
DOI: 10.1038/s41598-021-82944-4
|View full text |Cite
|
Sign up to set email alerts
|

Domeless receptor loss in fat body tissue reverts insulin resistance induced by a high-sugar diet in Drosophila melanogaster

Abstract: Insulin resistance is a hallmark of type 2 diabetes resulting from the confluence of several factors, including genetic susceptibility, inflammation, and diet. Under this pathophysiological condition, the dysfunction of the adipose tissue triggered by the excess caloric supply promotes the loss of sensitivity to insulin at the local and peripheral level, a process in which different signaling pathways are involved that are part of the metabolic response to the diet. Besides, the dysregulation of insulin signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 69 publications
3
15
0
Order By: Relevance
“…This results in inhibition of glucose consumption by muscles and the redirection of available energy to haemocytes, which is required during defence against pathogen infection ( Gallant, 2013 ; Zhao and Karpac, 2017 ). The results obtained by Lourido et al (2021) also support supposition about the close relationships between JAK/STAT and ILPs in the regulation of insect metabolism. These authors showed that loss of the Domless receptor (part of JAK/STAT pathway) in the fat body of D. melanogaster reverses hyperglycaemia and increases the expression level of the insulin resistance marker nlaz in larvae on a high sugar diet.…”
Section: Metabolic Processes Regulated By Ilpssupporting
confidence: 73%
“…This results in inhibition of glucose consumption by muscles and the redirection of available energy to haemocytes, which is required during defence against pathogen infection ( Gallant, 2013 ; Zhao and Karpac, 2017 ). The results obtained by Lourido et al (2021) also support supposition about the close relationships between JAK/STAT and ILPs in the regulation of insect metabolism. These authors showed that loss of the Domless receptor (part of JAK/STAT pathway) in the fat body of D. melanogaster reverses hyperglycaemia and increases the expression level of the insulin resistance marker nlaz in larvae on a high sugar diet.…”
Section: Metabolic Processes Regulated By Ilpssupporting
confidence: 73%
“…For example, HSD-fed flies contributed to confirmation of the involvement of the JAK/STAT pathway in the development of obesity and diabetes [ 133 ]. It was recently found that the loss of the JAK/STAT pathway receptor domeless in the fat body was able to reverse, at least in part, the dysmetabolism induced by a high sugar diet [ 134 ].…”
Section: Drosophila As a Diabetes Modelmentioning
confidence: 99%
“…Adult flies fed a high fat or high sugar diet for 7–14 days have higher lipid levels and altered insulin and glucose homeostasis (Birse et al, 2010 ; Musselman et al, 2011 ; May et al, 2019 ; Wilinski et al, 2019 ; Lourido et al, 2021 ), as well as changes in the levels of hundreds of metabolites, including amino acids, 1-Carbon metabolism, and nucleotides, organic acids, and overall carbon-nitrogen balance, depending on the type and length of diet exposure (Heinrichsen et al, 2014 ; Wilinski et al, 2019 ; Figures 1 , 2 ). These metabolic phenotypes reflect hallmarks of metabolic syndrome, and despite differences in anatomy compared to vertebrates, they contribute to defects in heart contractility and structure (Birse et al, 2010 ; Na et al, 2013 ) and in the function of the malpighian tubules; they also shorten lifespan (Na et al, 2013 ; Jung et al, 2018 ) and lower the resistance to other metabolic stresses (Heinrichsen and Haddad, 2012 ).…”
Section: The Effect Of High Fat and High Sugar Diets On D Melanogaster Behaviorsmentioning
confidence: 99%
“…These metabolic phenotypes reflect hallmarks of metabolic syndrome, and despite differences in anatomy compared to vertebrates, they contribute to defects in heart contractility and structure (Birse et al, 2010 ; Na et al, 2013 ) and in the function of the malpighian tubules; they also shorten lifespan (Na et al, 2013 ; Jung et al, 2018 ) and lower the resistance to other metabolic stresses (Heinrichsen and Haddad, 2012 ). The similarities in metabolic and physiological outcomes are perhaps not surprising considering that they are the result of the activation of conserved nutrient-sensing pathways, such as insulin-Target of Rapamycin (TOR; Birse et al, 2010 ; Li et al, 2010 ), hexosamine biosynthesis (Na et al, 2013 ; May et al, 2019 ), and Janus Kinases-Signal Transducer and Activator of Transcription proteins (JAK-STAT; Yu et al, 2018 ; Lourido et al, 2021 ). As in mammals, flies fed with these diets also show alterations in genes involved in immune response, inflammation, metabolism, neural signaling, synaptic function, and sensory perception in the brain and specific populations of neurons (Hemphill et al, 2018 ; Jung et al, 2018 ; May et al, 2019 ; Stobdan et al, 2019 ; Vaziri et al, 2020 ); some of these variations in gene expression have been causally linked to neural and behavioral changes, while others only remain correlated.…”
Section: The Effect Of High Fat and High Sugar Diets On D Melanogaster Behaviorsmentioning
confidence: 99%